Evaluation of Eye Alignment before and after Cataract Surgery. Issue 3 (3rd July 2021) - Ito, Misae; Saito, Anna; Ikeda, Tetsuya; Shimizu, Kimiya
ABSTRACT: Purpose : To assess changes in eye alignment before and after cataract surgery. Subjects and methods : The medical records of 786 cataract patients without eye movement limitation who underwent bilateral cataract surgery under topical anesthesia with monofocal IOL placement were retrospectively reviewed at the Eye Center of Sanno Hospital in Japan. Results : Before cataract surgery, 121 of the 786 patients (15.4%) had constant strabismus, 263 (33.5%) had intermittent strabismus, and 402 (51.1%) had phoria. Among the 121 patients with constant strabismus on the preoperative exam, 64 (52.9%) had exotropia without vertical strabismus, 7 (5.8%) had esotropia without vertical strabismus, and 6 (5.0%) had vertical strabismus without a horizontal component. After surgery, 98 of the 786 patients (12.5%) had constant strabismus, 126 (16.0%) had intermittent strabismus, 562 (71.5%) had phoria. The rate of eye alignment agreement before and after surgery was 72.3% overall. We found that 17 patients (2.2%) who did not have constant strabismus preoperatively developed constant strabismus postoperatively, and all of these patients experienced binocular diplopia. Characteristics of patients at risk for constant strabismus and diplopia postoperatively included patients with vertical deviation preoperatively (intermittent or phoria). Conclusions : Uncomplicated cataract surgery under topical anesthesia did not influence eye alignment classification in 72.3% of patients; however, patients with vertical deviation preoperatively were more likely to transition to constant strabismus after surgery.